Ion channel gates: comparative analysis of energy barriers. - Tai, K; Haider, S; Grottesi, A; Sansom, MS (2009)
The energetic profile of an ion translated along the axis of an ion channel should reveal whether the structure corresponds to a functionally open or closed state of the channel. In this study, we explore the combined use of Poisson-Boltzmann electrostatic calculations and evaluation of van der Waals interactions between ion and pore to provide an initial appraisal of the gating state of a channel. This approach is exemplified by its application to the bacterial inward rectifier potassium channel KirBac3.1, where it reveals the closed gate to be formed by a ring of leucine (L124) side chains. We have extended this analysis to a comparative survey of gating profiles, including model hydrophobic nanopores, the nicotinic acetylcholine receptor, and a number of potassium channel structures and models. This enables us to identify three gating regimes, and to show the limitation of this computationally inexpensive method. For a (closed) gate radius of 0.4 nm < R < 0.8 nm, a hydrophobic gate may be present. For a gate radius of 0.2 nm < R < 0.4 nm, both electrostatic and van der Waals interactions will contribute to the barrier height. Below R = 0.2 nm, repulsive van der Waals interactions are likely to dominate, resulting in a sterically occluded gate. In general, the method is more useful when the channel is wider; for narrower channels, the flexibility of the protein may allow otherwise-unsurmountable energetic barriers to be overcome.